ANALISIS PENGARUH KEBUTUHAN AKTUALISASI DIRI, PENGHARGAAN DAN KEBUTUHAN SOSIAL TERHADAP PENGEMBANGAN KARIR (Survei pada PT. Bukit Angkasa Makmur Bengkulu Tengah) - Tezar Arianto; Ervina Erlita (UNIVED Press, 2021)
This study uses data collection methods through interviews, observations and questionnaires. The population in this study were all employees at PT. Bukit Angkasa Makmur Bengkulu Tengah as many as 318 employees and sampling using simple random sampling method. Processing and analyzing data using validity and reliability tests. Then a conclusion was drawn using multiple linear regression statistical tests and analyzed its effects simultaneously (F test) and partially (t test). Based on the test results that the Need for Self-Actualization, Appreciation and Social Needs together (simultaneously) have an effect on Career Development.